Treating organic cyanide-containing groundwater by immobilization of a nitrile-degrading bacterium with a biofilm-forming bacterium using fluidized bed reactors - An, Xuejiao; Cheng, Yi; Huang, Mingyan; Sun, Yueling; Wang, Hailan; Chen, Xi; Wang, Jinming; Li, Dapeng; Li, Chunyan (Environmental pollution (1987), 2018)
Organic cyanide are widely used as an ingredient in the production of plastics, synthetic rubbers, polymers, pharmaceuticals and pesticides or used in laboratories and industries as solvents. Although nitrile-containing wastewater is subjected to primary and secondary treatments, residual nitriles may slowly seep and further migrate through groundwater, resulting in the micropollution of groundwater by organic pollutants. In this study, water samples were collected from different study areas in North China during a period of 3y (from 2013 to 2015) and analyzed to evaluate organic cyanide (CN−) contamination in groundwater. Three parallel lab-scale fluidized bed reactors (FBRs) were tested for their ability to remove organic cyanide from groundwater. The organic cyanide concentration in groundwater increased significantly (P < 0.05) from 2013 to 2015. With an optimal hydraulic residence time (HRT) of 54 min, reactor R3 (inoculated with a nitrile-degrading bacterium, BX2, and a biofilm-forming bacterium, M1) effectively removed 99.8% of CN− under steady operation, which was better than that of other reactors. Short-term shutdowns of FBRs had no serious effects on the efficiency of treating organic cyanide. This work demonstrated that the biofilm-forming bacterium could facilitate the fixation of nitrile-degrading bacterium and enhance the efficiency of removing organic cyanide from groundwater. [Display omitted] •Continuous monitoring of organic cyanide-containing groundwater was first reported.•Nitrile-degrading bacterium and biofilm-forming bacterium were used in FBR start-up.•Biofilm promoted the immobilization of nitrile-degrading bacterium.•Biofilm improved the efficiency of removing organic cyanide from groundwater.•Short-term shutdowns had no serious effect on FBR performance. This report is the first case of continuously monitoring organic cyanide-contaminated groundwater.